Microstructure, crystallization and dynamic mechanical behaviour of poly(vinylidene fluoride) composites containing poly(methyl methacrylate)- grafted multiwalled carbon nanotubes - Wang, M. (2014)
10.1088/0957-4484/18/23/235701